Hepatic Rupture as the Initial Presentation of an EGFR-Mutated Lung Adenocarcinoma: A Case Report - Mirallas, Oriol; Bosch-Schips, Marc; Pardo, Nuria; Aubanell, Anton; Salcedo-Allende, Maria Teresa; Callejo, Ana; Iranzo, Patricia; Tabernero, Josep; Felip, Enriqueta (Frontiers in Oncology, 2022)
Hepatic rupture is a rare complication of solid tumor malignancies, notably in lung adenocarcinomas, and carries an extremely poor overall prognosis. Epidermal growth factor receptor (EGFR) mutations in lung adenocarcinoma predict benefit with tyrosine kinase inhibitors (TKIs). This case report describes a female patient who presented with a metastatic hepatic rupture, and was subsequently diagnosed with EGFR-mutated lung adenocarcinoma. The tumor had an impressive response to TKI inhibitor treatment, reversing her extremely poor, short-term prognosis. We believe this unique case sheds light on the treatment management of hepatic ruptures and supports the high response rate seen with TKIs in EGFR-mutated lung cancers, regardless of the patient’s performance status.